To simplify the expression \((\frac{1}{2}x^2 - 3x + 2.25) + (0.75x^2 + 2x - \frac{1}{4})\), we first combine like terms.
Step 1: Combine the \(x^2\) terms. \[ \frac{1}{2}x^2 + 0.75x^2 \] Convert \(0.75\) to a fraction: \[ 0.75 = \frac{3}{4} \] So we rewrite the term: \[ \frac{1}{2} = \frac{2}{4} \quad \text{(to have the same denominator)} \] Adding these: \[ \frac{2}{4}x^2 + \frac{3}{4}x^2 = \frac{5}{4}x^2 \]
Step 2: Combine the \(x\) terms. \[ -3x + 2x = -x \]
Step 3: Combine the constant terms. \[ 2.25 - \frac{1}{4} \] Convert \(2.25\) to a fraction: \[ 2.25 = \frac{9}{4} \] Now subtract: \[ \frac{9}{4} - \frac{1}{4} = \frac{8}{4} = 2 \]
Final Step: Combine everything together. Putting it all together, we have: \[ \frac{5}{4}x^2 - x + 2 \]
Thus, the simplified expression is: \[ \frac{5}{4}x^2 - x + 2 \]